‘Explicit’ and ‘implicit’ non-local continuous descriptions for a plate with circular inclusion in tension - Tuna M.; Leonetti L.; Trovalusci P.; Kirca M. (Springer Science and Business Media LLC, 2019)
Increasing application of composite structures in engineering field inherently speed up the studies focusing on the investigation of non-homogeneous bodies. Due to their capability on capturing the size effects, and offering solutions independent of spatial discretization, enriched non-classical continuum theories are often more preferable with respect to the classical ones. In the present study, the sample problem of a plate with a circular inclusion subjected to a uniform tensile stress is investigated in terms of both ‘implicit’/‘weak’ and ‘explicit’/‘strong’ non-local descriptions: Cosserat (micropolar) and Eringen theories, by employing the finite element method. The material parameters of ‘implicit’ model is assumed to be known, while the nonlocality of ‘explicit’ model is optimized according to stress concentration factors reported for infinite Cosserat plates. The advantages/disadvantages, and correspondence/non-correspondence between both non-local models are highlighted and discussed apparently for the first time, by comparing the stress field provided for reference benchmark problem under various scale ratios, and material parameter combinations for matrix-inclusion pair. The results reveal the analogous character of both non-local models in case of geometric singularities, which may pave the way for further studies considering problems with noticeable scale effects and load singularities.
Keywords: Cosserat; Eringen; Finite elements; Non-local models; Nonhomogeneous solids; Scale effects